2021
DOI: 10.1002/app.51486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of difunctional reactive polyhedral oligomeric silsesquioxane on the properties of EPDM

Abstract: Bifunctional reactive polyhedral oligomeric silsesquioxane (POSS) of 3, 13‐divinyl octyphenyl silsesquioxane (DV‐DDSQ) and 3, 13‐dihydro octyphenyl silsesquioxane (DH‐DDSQ) were used as additive to modify ethylene‐propylene‐diene rubber (EPDM), and double vinyl groups or active hydrogen groups of bifunctional reactive POSS (brPOSS) underwent a cross‐linking reaction with the active hydrogen groups and double bonds of EPDM, to investigate the effect of brPOSS regulating functional reaction group on the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The mechanisms are of important significance to the studying of the materials' structural relaxation. 39,40 In the previous study of the mechanism of physical aging, there are two different process been found which follow different mathematical relationshiops 41,42 : one is the fast mechanism, which displays Arrhenius temperature dependence with low activation energy; while the other is the slow mechanism, which follows the super-Arrhenius temperature dependence. 43 For the neat PMMA, only one peak appears in Figure 7, since the fast recovery mechanism is thickness dependent and compatible with the assumption of the diffusion of the free volume holes toward surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms are of important significance to the studying of the materials' structural relaxation. 39,40 In the previous study of the mechanism of physical aging, there are two different process been found which follow different mathematical relationshiops 41,42 : one is the fast mechanism, which displays Arrhenius temperature dependence with low activation energy; while the other is the slow mechanism, which follows the super-Arrhenius temperature dependence. 43 For the neat PMMA, only one peak appears in Figure 7, since the fast recovery mechanism is thickness dependent and compatible with the assumption of the diffusion of the free volume holes toward surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…After vulcanization, the ablative performance of the composite was also significantly increased; DH-DDSQ was superior to DV-DDSQ to improve the overall performance of EPDM. [129] 3 | APPLICATIONS OF ORGANOSILICON-FUNCTIONALIZED POLYOLEFIN…”
Section: Coordination Polymerizationmentioning
confidence: 99%
“…Hao et al 29 and Ma et al 28 prepared and investigated EPDM composites with octa vinyl POSS or div-POSS for the mechanical and ablative properties, the tensile strength of the composites were decreased by 3.03% and 35.8%, the linear ablation rates of the composites were reduced by 21% and 38.2% by the adding of 5 phr octa vinyl POSS or div-POSS, respectively, which was demonstrated POSS with different functionalities present various degrees of improvement in the mechanical and thermal properties of EPDM composites. 27,28,30 Therefore, it is worthwhile to be explored that the relationship between the functionality and cage structure of POSS and the mechanical and ablative properties of EPDM composites, which is the novelty and originality of this paper.…”
Section: Introductionmentioning
confidence: 98%